THE INFLUENCE OF THE 1998 ASIAN BANKING CRISIS AND THE 2008 GLOBAL FINANCIAL CRISIS TO GROWTH OF THE THIRD PARTY FUNDS OF BANKING SECTOR IN INDONESIA - Nurfaidah, Rani; Hastuti, Fitri (Asosiasi Fakultas Ekonomi dan Bisnis Indonesia, 2018)
The purpose of this research is to investigate the influence of macroeconomic fundamentals such as real GDP growth, deposit rate, and return of composite stock price index, and the influence of bank performance such as the growth of secondary reserve and Non Performing Loans to Third Party Funds. The growth of the banking sector in Indonesia in the 1998 Asian Banking Crisis and the 2008 Global Financial Crisis and also to analyze the different influence of independent variables to Third Party Funds growth in both crises. The data used are secondary data with the research object of 101 banks which were established in both crises consistently. The method which is used in this study is the pooled EGLS (Cross-Section Weight) and fixed effect method. The results show that macroeconomic fundamentals such as real GDP growth, deposit rate, and return of IHSG have significant effect to growth of Third Party Funds, and bank performance such as the growth of secondary reserve has a significant effect while NPL has no significant effect to growth of Third Party Funds in both crises. Besides that, there is a different effect of each independent variable in both crisis periods where all the independent variables in the period of the 1998 Asian Banking Crisis is not according to the theory, while all of the independent variables in the period of the 2008 Global Financial Crisis is according to the theory. JEL Classification: E50, G01, G21 Keywords: Banking Performance, Crisis, Cross-Section Weight,Macroeconomic Fundamentals Third Party Funds Growth